2022
DOI: 10.3390/s22145266
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Influence of Environmental Conditions on Automotive Lidar Sensors

Abstract: Safety validation of automated driving functions is a major challenge that is partly tackled by means of simulation-based testing. The virtual validation approach always entails the modeling of automotive perception sensors and their environment. In the real world, these sensors are exposed to adverse influences by environmental conditions such as rain, fog, snow, etc. Therefore, such influences need to be reflected in the simulation models. In this publication, a novel data set is introduced and analyzed. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Future work could include the production of a better quality dataset (especially for smoke). The inference model could also be trained and tested on real outdoor acquisitions, with for example the dataset proposed in [36]. Finally, the temporal evolution of visibility could be taken into account to improve the classification over time, with for example a Bayesian histogram filter.…”
Section: Discussionmentioning
confidence: 99%
“…Future work could include the production of a better quality dataset (especially for smoke). The inference model could also be trained and tested on real outdoor acquisitions, with for example the dataset proposed in [36]. Finally, the temporal evolution of visibility could be taken into account to improve the classification over time, with for example a Bayesian histogram filter.…”
Section: Discussionmentioning
confidence: 99%
“…During rainfalls, sensing efficacy began to decline at a rainfall intensity of 10 mm/h, and at 50 mm/h, target detection was essentially nullified. However, it was observed that varying levels of snowfall did not lead to a marked decline in the LiDAR’s sensing capabilities [ 24 ]. Recently, many researchers have been researching to improve the recognition rate of autonomous driving by converging LiDAR and image sensors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…al.’s studies show that LiDAR’s intensity for cars and people or LiDAR’s point-cloud density decreases in fog and rain situations. In adverse weather, the point-cloud-based recognition study was solved by changing the network structure or input expression by analyzing data characteristics [ 15 , 24 , 25 , 26 ].…”
Section: Related Workmentioning
confidence: 99%